Evaluating the performance of flow-electrode capacitive deionization for cadmium removal from aqueous solution. (April 2022) - Gong, Weijia; Yang, Ya; Chang, Haiqing; Wang, Tianyu; Liang, Heng
Abstract: Cadmium (Cd 2+ ) polluted water causes harmful impact to human beings, life and the natural ecological environment. It is necessary to develop environmentally friendly treatment process for Cd 2+ removals. In this study, flow-electrode capacitive deionization (FCDI) technology was proposed to treat Cd 2+ -containing aqueous solutions. The performance of FCDI in removing Cd 2+ under various operating conditions was investigated, including the initial Cd 2+ concentration, pH values and applied voltage, as well as the long-term operation behavior. The results showed that 50% of Cd 2+ was removed at an initial concentration of 10 mg/L, and increased initial Cd 2+ concentrations resulted in lower removal efficiencies. The pH of the solution significantly influenced removal efficiency, and the highest Cd 2+ removal (54%) was observed at pH of 3. With the increase of applied voltage, the removal efficiency of Cd 2+ by FCDI system increased, with a peak of 46.6% at 2.4 V. Then, the multi-cycle operation experiments demonstrated that a stable Cd 2+ removal was achieved using FCDI. Multiple characterizations of activated carbon electrode before and after the experiment showed that the surface functional groups of activated carbon did not change after adsorbing Cd 2+ . The results obtained in this work indicated that FCDI can remove Cd 2+ effectively and stably. Graphical abstract: Unlabelled Image Highlights: The effect of operation conditions on Cd 2+ removal using FCDI was investigated. The Cd 2+ removal was greatly influenced by concentration, pH and applied voltage. FCDI can effectively remove heavy metal cadmium from aqueous solution. A stable Cd 2+ removal was achieved using FCDI via multi-cycle operation.